Management of Dislocation of the Shoulder Joint with Ipsilateral Humeral Shaft Fracture: Initial Experience. Issue 5 (19th August 2020) - Lyu, Fei; Wang, Hui‐xiang; Bi, Chun; Shen, Shu‐ming; Wang, Qiu‐gen; Wu, Xiao‐ming
Abstract : Objective: To gain a better understanding of the traumatic mechanism and to develop appropriate treatment for dislocation of the shoulder joint with an ipsilateral humeral shaft fracture. Methods: This was an observational and descriptive study. Nine patients with traumatic shoulder dislocations associated with ipsilateral humeral shaft fractures who visited the emergency room and received treatment from January 2012 to June 2018 were retrospectively analyzed. CT with three‐dimensional reconstruction was performed to provide precise anatomical information of the fractures. The traumatic event and the type of fracture of the humeral shaft were analyzed to help determine the trauma mechanism. Closed reduction of the dislocation was attempted at once under intravenous anesthesia. One patient died the following day due to unrelated causes. All humeral shaft fractures of the eight patients received internal fixation, and then reduction of the dislocation was performed again if previous attempts failed. The affected limb was immobilized in a sling for 3 weeks postoperatively, and then active and passive movement was encouraged. Patients were evaluated based on clinical and radiographic examinations, shoulder joint range of motion, Constant–Murley score, and subjective shoulder value. Results: Four cases in the present study could not give a clear description of the traumatic procedure. The other five patients suffered a second strike on their upper arms when they were hurt, with low mobility and high pain in the shoulder region. Seven cases were simple fractures and two were wedge fractures. According to the AO/OTA classification system, four cases were type 12‐A2, three were type 12‐A3, and two were type 12‐B2. Six patients successfully obtained closed manipulative reduction of the shoulder dislocation in the acute stage. The follow‐up time ranged from 18 to 31 months. No deep wound infections were encountered. All fractures healed uneventfully. The union time ranged from 4 to 6 months. At the final follow‐up, shoulder range‐of‐motion values were found to range from 140° to 170° forward flexion, 30° to 40° extension, 40° to 45° adduction, 150° to 170° abduction, 50° to 60° internal rotation, and 50° to 60° external rotation; no recurrent instability of the shoulder joint occurred; the Constant–Murley score was 89.5 ± 3.7 points (range: 84–94 points); the subjective shoulder value was 89.4% ± 6.3% (range: 75%–95%). Conclusion: Shoulder dislocation most likely occurs first with an axial force or a direct posteroanterior force and a subsequent force results in the shaft fracture. For patients with mid‐distal humerus fractures, closed manipulative reduction of the joint is usually effective. After success of closed reduction, surgery for the humeral shaft fracture is advocated to ensure stability and to make patient nursing convenient. In cases with fractures in the proximal third of the humeral shaft, fixation is suggested beforehand to help reduce the shoulder dislocation. Abstract : To describe a treatment strategy for shoulder dislocation associated with a concomitant ipsilateral humeral shaft fracture.